Individual and organizational perspectives on emotion management and display - Zerbe, W. J.; Ashkanasy, Neal M., 1945-; Härtel, Charmine E. J., 1959- (Emerald, 2006)
Affect and emotion have been recognized as important factors in understanding behavior in organizations, as evidenced by the increasing frequency of special journal issues, themed conferences, and books and articles devoted to the topic. The articles in this volume represent a selection of the best papers presented at the Fourth International Conference on Emotions and Organizational Life (which was held in London, England, in June, 2004), together with invited papers by some of leading scholars in the field. The theme of this volume, Individual and Organizational Perspectives on Emotion Management and Display, concerns the management by organizations of the emotions of employees and the effects on individuals.-It begins by looking at the effective self-management of emotion and how leaders can use emotions, intelligently and sometimes paradoxically, to foster effective personal and team outcomes, and goes on to examine the nature of emotionally charged incidents between employees and supervisors. The effective management of emotion is particularly relevant to organizational outcomes in service organizations. Specific chapters look at emotion work performed by employees in hospitality and healthcare organizations, and others consider the role that culture plays in the perceptions of service workers regarding emotion work. Others examine the critical interplay between characteristics of employees, organizational practices, and the emotions that customers experience when service encounters go awry.-Finally the volume comes full circle in an examination of how the thinking strategies individuals use can foster 'adaptive emotions' and more emotionally intelligent, constructive responses to workplace stressors. This book features a selection of the best papers presented at the Fourth International Conference on Emotions and Organizational Life (London, UK, June, 2004). It represents a cross-section of cutting-edge research in the field and includes contributions from established leading scholars as well as the 'rising stars' in the field.
Keywords: Emotions.; Affect (Psychology); elektronické knihy; electronic books